Impact of Vaccination on Haemophilus influenzae Type b Carriage in Healthy Children Less Than 5 Years of Age in an Urban Population in Nepal. (1st September 2021) - Shrestha, Sonu; Stockdale, Lisa K; Gautam, Madhav C; Gurung, Meeru; Feng, Shuo; Maskey, Pratistha; Kerridge, Simon; Kelly, Sarah; Voysey, Merryn; Pokhrel, Bhishma; Rajbhandari, Piyush; Thorson, Stephen; et al.
Abstract: Background: Reduction in detection of asymptomatic carriage of Haemophilus influenzae type b (Hib) can be used to assess vaccine impact. In Nepal, routine vaccination against Hib in children at 6, 10, and 14 weeks of age was introduced in 2009. Before vaccine introduction, Hib carriage was estimated at 5.0% among children aged <13 years in Nepal, with higher rates among children under 5. Large-scale evaluation of Hib carriage in children has not been investigated since the introduction of the pentavalent diphtheria-tetanus-pertussis/Hib/hepatitis B (DTP-Hib-HepB) vaccine in Nepal. Methods: A total of 666 oropharyngeal swabs were collected between August and December 2018 from healthy children between 6 months and 5 years of age attending the vaccination clinic at Patan Hospital, Kathmandu, Nepal. Of these 666 swabs, 528 (79.3%) were tested for Hib by culture. Demographic and vaccination data were collected. Results: Among 528 swabs tested for Hib, 100% came from fully vaccinated children. No swabs were positive for Hib (95% confidence interval, .0–.7). The absence of Hib in 2018 suggests vaccine-induced protection against Hib carriage 9 years after vaccine introduction. Conclusions: Following 3 doses of pentavalent DTP-Hib-HepB vaccine, Hib carriage in children under the age of 5 years in Nepal is no longer common. Ongoing high coverage with Hib vaccine in early childhood is expected to maintain protection against Hib disease in Nepal.